2021
DOI: 10.1016/j.bbr.2020.113068
|View full text |Cite
|
Sign up to set email alerts
|

Increased alcohol self-administration following exposure to the predator odor TMT in active coping female rats

Abstract: Post-traumatic stress disorder (PTSD) and alcohol use disorder (AUD) are highly comorbid. Additionally, individual differences in response to stress suggest resilient and susceptible populations. The current study exposed male and female Long Evans rats to the synthetically produced predator odor 2,5-dihydro-2,4,5-trimethylthiazoline (TMT) to examine individual differences in stress-reactive behaviors (digging and immobility) and whether these differences could predict lasting consequences of TMT and increases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 57 publications
8
44
0
Order By: Relevance
“…In the present work, during re-exposure to the previously TMT-paired context, rats engaged in behavioral responses, such as defensive digging and decreased immobility to a greater extent than controls, indicative of context reactivity. This finding is consistent with previous work (Ornelas et al, 2020;Shallcross et al, 2019;Tyler et al, 2020). In Experiment 1, in which bedding was provided in the context, this was evidenced by increased digging and reduced immobility behavior (i.e., greater mobility) relative to controls during the context re-exposure.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present work, during re-exposure to the previously TMT-paired context, rats engaged in behavioral responses, such as defensive digging and decreased immobility to a greater extent than controls, indicative of context reactivity. This finding is consistent with previous work (Ornelas et al, 2020;Shallcross et al, 2019;Tyler et al, 2020). In Experiment 1, in which bedding was provided in the context, this was evidenced by increased digging and reduced immobility behavior (i.e., greater mobility) relative to controls during the context re-exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, avoidance of the TMT-paired side of the chamber was not observed during context reexposure in either experiment. This is not altogether surprising given that it has been shown that although TMT produces significant avoidance behavior during exposure, TMT has not been shown to induce context conditioning through avoidance behavior (Ornelas et al, 2020;Rosen et al, 2015). Additionally, these data are in accordance with previous work from our lab (Ornelas et al, 2020) and others (Schwendt et al, 2018) that show TMT can produce contextual conditioning.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations